Efectes de les infraestructures elèctriques sobre els ocells a l’EIN de Ardenya-Cadiretes - Funosas Planas, Gerard (2015)
The large stretch of power lines that are found in our landscapes has an effect on the environment they surround, and one of their most important impacts are the accidents with the bird community, either by electrocution or collision. The most affected group are the birds of prey, given that they frequently use the electric posts for perching and, in general, they are species with reduced populations and with an improvable conservation status. This project aims to analyse these problems in the mountain range of Ardenya or Cadiretes, located in the Catalan coast, between the regions of la Selva, el Gironès and el Baix Empordà. Its geological singularity and its natural heritage have included that area as a PEIN, and made the region a favourable habitat for some endangered raptor species associated with rock massifs, as the great owl (Bubo bubo), the peregrine falcon (Falco peregrinus) or the bonelli’s eagle (Aquila fasciata). Due to that fact, during the months of February and March, about 40 km of the high power lines were sampled, corresponding to the 70% of their total expanse. Electrocution evidences (as groups of feathers, corpses or rests of carcasses) have been searched under the utility pole, which have been geo located, photographed and catalogued according to their potential danger. This classification has been done taking into account an assembly of variables, related to the tower configuration and also to the environment their surround, following the methodology done by Tintó et al. (2010). We’ve found few electrocution evidences, with a sample unit of 4, for all the 357 utility poles sampled. Nevertheless, the result value is considered a lot lower than the actual would be, and its explanation would be allocated by the carnivorous mammals which move away the bird corpses. This statement is reinforced by the excrements of those found regularly on the posts bases, which demonstrate their recurrence under the power lines. At the same time, the virtually totality of high power lines have been placed in a map, and some corrective measures have been designed for the 9 most dangerous utility poles, from a conservative insight. Two specific censuses for studying the raptors community have been done, which considered together with the observations brought by other bibliographic sources, have given an 18 species list of birds of prey that inhabit in the mountain range or that may frequent it